Management Modeling Including Process Quality and Technology for Service Improvement by Applying Structural Equations - Gonzales Lovón, Rosario (2022)
This study proposes a model to improve identity registration service and correlates this service to the process quality and technology by means of structural equations using SPSS and AMOS. To reinforce the analysis of the information obtained from documents and records of the processes of identity registration, a 21 question survey was given to citizens coming to 1 of 16 regional headquarters, from which it was possible to demonstrate through structural equations, the existence of a strong relationship between the three variables: process quality, technology and service improvement.